2019
DOI: 10.1111/jfb.13944
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure of the blue jack mackerel Trachurus picturatus across its western distribution

Abstract: Blue jack mackerel Trachurus picturatus collected at six sampling locations of the north-east Atlantic Ocean (Azores, Madeira, Canaries, and Matosinhos, Peniche and Portimão, mainland Portugal) and one location in the Mediterranean (Sicily), were used to examine the genetic structure of this species. Three mitochondrial gene regions (cytochrome c oxidase subunit I, cytochrome b and control region) were used to study the genetic structure of the species in Macaronesia, as well as to compare the genetic diversit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…This aligns with the previous T. trachurus study by Kasapidis & Magoulas (), which found no significant structure across a more extensive sampling of NE Atlantic and Mediterranean waters using four of the microsatellites employed here. Genetic cohesion between Atlantic and Mediterranean samples is also described for other horse mackerel species and indicates that the Almeria‐Oran frontal system is not a prominent phylogeographic break in this group (Comesana et al ., ; Moreira et al ., ). Nuclear F ST tests performed for both the null allele corrected and the subset of HWE conforming loci and mtDNA Φ ST broadly supported a lack of differentiation of the Ghana sample from the other T. trachurus samples.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This aligns with the previous T. trachurus study by Kasapidis & Magoulas (), which found no significant structure across a more extensive sampling of NE Atlantic and Mediterranean waters using four of the microsatellites employed here. Genetic cohesion between Atlantic and Mediterranean samples is also described for other horse mackerel species and indicates that the Almeria‐Oran frontal system is not a prominent phylogeographic break in this group (Comesana et al ., ; Moreira et al ., ). Nuclear F ST tests performed for both the null allele corrected and the subset of HWE conforming loci and mtDNA Φ ST broadly supported a lack of differentiation of the Ghana sample from the other T. trachurus samples.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear F ST tests performed for both the null allele corrected and the subset of HWE conforming loci and mtDNA Φ ST broadly supported a lack of differentiation of the Ghana sample from the other T. trachurus samples. Although there was a gap in our sampling between Ghana and Europe, high gene flow between European and north‐west African sites is also suggested for the blue jack mackerel ( T. picturatus ) (Moreira et al ., ). The available data therefore indicate that T. trachurus exhibits high gene flow and an absence of genetic structure across most of its sampled range to date.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although molecular markers, namely mtDNA, show weak genetic structure among marine pelagic fish (Chlaida et al 2009;Kasapidis et al 2012;Moreira et al 2019b), a single stock of S. colias has been considered until now for the Northeast Atlantic (Scoles et al 1998;Zardoya et al 2004). However, the present results showed significant regional differences in body geometric morphometrics and otolith-shape analyses of individuals collected in the North-east (ICES IXa and X) and eastern Centre (CECAF 34.1.2) Atlantic fishing areas for the species.…”
Section: Discussionmentioning
confidence: 99%